ANALYSING THE PRE-COMPETITION ANXIETY AMONG BASKETBALL PLAYERS UNDER EIGHTEEN BASED ON THEIR POSITIONS - Yaw Teck Hing; Pathmanathan A/L Suppiah; Hasnol Noordin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Psychological factors are some of the factors influencing a player’s achievement in basketball tournaments. A survey study was conducted to compare the pre-competition anxiety level based on the playersâ€™ positioning among 144 male basketball players who are under 18 years old in Sabah. The Competitive State Anxiety Inventory-2 (CSAI-2) which was translated into the Malay language was used as the main instrument in this study along with the Kruskal-Wallis Test. The findings indicated that there is no significant difference in the pre-competition anxiety level among the players based on their positioning Ï‡2(2) = 3.742, p = .154 (p> .05). The findings of the cognitive anxiety subscale also were found to be insignificant based on the positioning; Ï‡2(2) = 1.938, p = .380 (p> .05). The somatic anxiety of the pre-competition findings also showed no difference based on the positions of players; Ï‡2(2) = 1.509, p = .470 (p> .05). Moreover, the values for subscale of confidence was also found to be insignificant; Ï‡2(2) = 1.565, p = .457 (p> .05). Therefore, the study found out that the environmental factors play a crucial role in reducing the basketball playersâ€™ pre-competition anxiety. The coaches and trainers should consider these environmental factors in improving their playersâ€™ pre-competition anxiety, thus allowing them to compete and perform at their best state of mind.